IMPROVING UNDERSTANDING OF MATHEMATICAL CONCEPTS THROUGH THE CONTEXTUAL TEACHING AND LEARNING MODEL FOR FOURTH GRADE STUDENTS AT SD 46 LUBUKLINGGAU - noni wulandari (Teaching and General Education Studies, 2026)
Mathematics learning in elementary schools often faces challenges such as students’ difficulty in understanding abstract concepts and low engagement during conventional learning methods, which affects their overall learning outcomes. This study aims to determine whether the Contextual Teaching and Learning (CTL) model can improve the understanding of mathematical concepts of grade IV Elementary School students.. This study was conducted at SDN 46 Lubuklinggau using Classroom Action Research (CAR), with the research subjects being 20 grade IV students. Data collection techniques included observation, documentation, and tests, while data analysis was carried out using quantitative descriptive analysis. The study consisted of two cycles, each consisting of four stages: planning, implementation, observation, and reflection. In cycle I, the pre-test percentage was 25% in the very low category, while the post-test increased to 60% in the moderate category. In cycle II, the pre-test was 40% in the low category, and the post-test showed a significant improvement to 85% in the very high category. The results indicate that the CTL model effectively enhances students’ understanding of mathematical concepts. This suggests that implementing the CTL model can increase students’ engagement, motivation, and ability to relate mathematical concepts to real-life situations. For future research, it is recommended to explore the CTL model in combination with digital learning tools to further enhance conceptual understanding and interactive learning in mathematics.